2005
DOI: 10.1177/0032329204272551
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Americanism and Americanization in Germany

Abstract: Contemporary German anti-Americanism is not a continuation of earlier anticapitalist, antimodern, and often anti-Semitic anti-Americanism. Rather, since the late 1960s a political anti-Americanism, which accepts capitalism and the extensive Americanization of German society, has emerged. It is a response to specific American foreign policies, but its roots lie in the uneven Americanization of twentieth-century Germany. Anti-Americanism has been fostered by Germany’s nonliberal variety of capitalism, by its mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Americanization, which sounds like an ageold concept, is being illuminated again as one of the important components of 'Cold War studies' since the mid-1990s. For example, Roper, Dean and Nolan deal with different cases of Americanization in different locations (Roper 1996;Dean 1997;Nolan 2005). We basically agree with the definition of Americanization by one of these authors, who argues that Americanization can be defined 'by the images and discourses that imagine or construct America as a model of economic, social and cultural development, as one possible, extremely powerful, and appealing model of modernity' (Nolan 2005: 90).…”
Section: Reconsidering Americanization In East Asiamentioning
confidence: 61%
“…Americanization, which sounds like an ageold concept, is being illuminated again as one of the important components of 'Cold War studies' since the mid-1990s. For example, Roper, Dean and Nolan deal with different cases of Americanization in different locations (Roper 1996;Dean 1997;Nolan 2005). We basically agree with the definition of Americanization by one of these authors, who argues that Americanization can be defined 'by the images and discourses that imagine or construct America as a model of economic, social and cultural development, as one possible, extremely powerful, and appealing model of modernity' (Nolan 2005: 90).…”
Section: Reconsidering Americanization In East Asiamentioning
confidence: 61%
“…First of all, we have demonstrated that negative views today are dependent on the specific historical traditions of the resentment: if a country has a strong history of anti-Americanism (such as Germany or France), higher levels of negative attitudes can be reported compared with countries that do not have such a history (especially Poland). Against this background, it seems highly problematic to consider anti-Americanism simply as a function of recent political conflicts (Cunliffe, 1986;Fabbrini, 2004;Nolan, 2005;Kohut and Stokes, 2006;Friedman, 2008;Holsti, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As we have mentioned, many explanations in recent works rest on a more or less subtle version of the assumption that anti-Americanism is a reaction to the peculiar position of the United States in world politics (Cunliffe, 1986;Fabbrini, 2004;Nolan, 2005;Kohut and Stokes, 2006;Friedman, 2008;Holsti, 2008). It is presumed that the aversion to the United States stems from its hegemonic character.…”
Section: What Drives Anti-americanism?mentioning
confidence: 99%
See 1 more Smart Citation
“…In Western Europe, the discourse of cultural resistance against the USA was fuelled by two main sources that converged at times: a rightward one, which sought to defend tradition and national identity from the corrosive influence of Americanism 35 and a leftward, which targeted American cultural imperialism as a vehicle for the broader political and economic aspirations of the USA. 36 The concept of Americanism was a central issue in the Greek Cold War ideological and propaganda confrontation. For the non-Communists, Americanism was synonymous with humanism, a realistic vision of prosperity.…”
Section: Latent Anti-americanism (1985-early 1990s)mentioning
confidence: 99%